Jacobi and Linear Stability Analysis of T Chaotic System - Shukla, Vijay K.; Yadav, Vijay K.; Kumar, Abhishek; Mishra, Prashant K. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, the stability analysis of T chaotic system has been discussed by two different methods viz., Jacobi stability and linear stability methods. Jacobi stability analysis of T chaotic system has been studied by using geometro-dynamical approach with Kosambi-Cartan-Chern (KCC) theory. The deviation curvature tensor and five KCC invariants are obtained which express the intrinsic properties of nonlinear dynamical system. The dynamical behaviors of deviation vector components near the equilibrium points of T system are also discussed. The phase portrait of deviation vector components reflects the dynamical behavior of T system, which shows the instability and chaotic behaviour near the equilibrium points for a set of parameters.